2016
DOI: 10.1177/0308022615612806
|View full text |Cite
|
Sign up to set email alerts
|

The development of a theory-informed workbook as an additional support for students on role-emerging placements

Abstract: (2016) The development of a theory-informed workbook as an additional support for students on role-emerging placements. British Journal of Occupational Therapy. ISSN 0308-0226. Link to official URL (if available):http://dx.doi.org/10.1177/0308022615612806This version is made available in accordance with publishers' policies. All material made available by CReaTE is protected by intellectual property law, including copyright law. Any use made of the contents should comply with the relevant law.Contact: create.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Collaborating with services unfamiliar with a profession's role, along with the emotional challenges of practice-based learning, were reported to affect professional identity (Dancza et al, 2013), and Cleak and Smith (2012) found that social work students who experienced long-arm supervision were significantly less satisfied with the learning experience. Dancza et al (2016) also identified that students receiving long-arm supervision needed additional support to compensate for less frequent contact with an educator. Linnane and Warren's (2017) survey of occupational therapists and students indicated that while the model was felt to be effective, there was apprehension associated with the lack of access to profession-specific role models and misunderstandings from host services on the student's role.…”
Section: Long-arm Supervisionmentioning
confidence: 99%
“…Collaborating with services unfamiliar with a profession's role, along with the emotional challenges of practice-based learning, were reported to affect professional identity (Dancza et al, 2013), and Cleak and Smith (2012) found that social work students who experienced long-arm supervision were significantly less satisfied with the learning experience. Dancza et al (2016) also identified that students receiving long-arm supervision needed additional support to compensate for less frequent contact with an educator. Linnane and Warren's (2017) survey of occupational therapists and students indicated that while the model was felt to be effective, there was apprehension associated with the lack of access to profession-specific role models and misunderstandings from host services on the student's role.…”
Section: Long-arm Supervisionmentioning
confidence: 99%
“…A search on current literature yielded only ten studies to date with the main focus on school-based occupational therapy practice in Europe (excluding studies for measurement validation). Out of these ten studies, five were conducted in England [15, 16, 2224], two in Ireland [25, 26], two in Sweden [27, 28], and one in Portugal [29].…”
Section: Introductionmentioning
confidence: 99%
“…They explored through a case study the joint working of occupational therapy and clinical psychology in a school setting. In the study of Dancza et al [22], the focus was on the implementation of role emerging placements of English occupational therapy students in school settings. In the Portuguese study, Maia et al [29] looked at interventions used by occupational therapists in schools to determine the most common intervention approaches and relevant aspects of the therapeutic process in schools.…”
Section: Introductionmentioning
confidence: 99%
“…This was an unexpected finding, given the potential of these placements to grow graduate employment opportunities and address the increasing oversupply of Australian occupational therapy graduates (McKinstry & Fortune, ). In the literature (Dancza, Copley, Rodger & Moran, ), a role emerging placement only occurs in an area where no occupational therapy service has been established, and the benefits of occupational therapy input have not been explored or recognised (Overton et al . ).…”
Section: Discussionmentioning
confidence: 99%